Setting up standardized interventions for HIV serodiscordant couples: a guide for healthcare providers and researchers - Mona Larki; Javad Moghri; Narjes Bahri; Robab Latifnejad Roudsari (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction In countries with generalized epidemics of human immunodeficiency virus (HIV), the negative individuals in serodiscordant relationships constitute the largest population at risk. This study was carried out to investigate setting up standardized interventions for HIV serodiscordant couples.